Analysis of rural households' wellbeing in Nigeria: a capability approach. Issue 9 (20th August 2014) - Oni, Omobowale Ayoola; Adepoju, Temitayo Adenike; Tyler, Colin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The purpose of this paper is to use the capability approach to analyse the well being of rural households in Nigeria and determine the factors that influence the well being status reported. Design/methodology/approach The paper analyses multidimensional wellbeing of the households in the capability space using data in seven dimensions obtained from the Nigeria Core welfare indices survey of 2006. The well being status of households was derived using the fuzzy set approach, while a logistic regression was used to isolate the factors that determine wellbeing. Findings The results of the fuzzy set analysis showed that overall rural households in Nigeria have a low mean well being status at 0.27. Capability to attain a desired state of well being is highest with respect to asset ownership and lowest with respect to security. The logistic analysis shows that the predicted probability of attaining the mean capability well being increases for male headed households, increasing educational level and age of the head, household size, and public service occupation. Originality/value This paper attempts to bridge the knowledge gap in the empirical literature of well being studies and specifically in the use of the capability approach and its application in the Nigerian well being context.